The Impact of Comprehensive Sexual Education on Adolescent Attitudes and Knowledge: Implications for Program Development and Policy - Stepahanie, Mutiara Glorya (Acta Psychologia, 2024)
This research explores the impact of sexual education on adolescents' attitudes and knowledge, aiming to inform program development, policy formulation, and practice within the field. Employing a mixed-methods approach, the study examines the effectiveness of a comprehensive sexual education program in a diverse urban setting. Participants, aged 13-18, were recruited from multiple secondary schools and divided into intervention and control groups. Quantitative analysis of pre-test and post-test surveys revealed significant improvements in sexual knowledge and attitudes among intervention group participants. Qualitative exploration through focus group discussions and interviews provided nuanced insights into the program's impact on attitudes, behaviors, and perceptions. The findings underscore the importance of comprehensive, inclusive, and evidence-based sexual education programs in promoting adolescent sexual health and well-being. Implications for program design, policy development, professional practice, collaboration, and advocacy are discussed. Overall, the study contributes to advancing sexual education efforts and empowering adolescents to make informed decisions about their sexual health.